A focus on extracellular Ca(2+) entry into skeletal muscle - Cho, Chung-Hyun (Exp Mol Med, 2017)
The main task of skeletal muscle is contraction and relaxation for body movement and posture maintenance. During contraction and relaxation, Ca(2+) in the cytosol has a critical role in activating and deactivating a series of contractile proteins. In skeletal muscle, the cytosolic Ca(2+) level is mainly determined by Ca(2+) movements between the cytosol and the sarcoplasmic reticulum. The importance of Ca(2+) entry from extracellular spaces to the cytosol has gained significant attention over the past decade. Store-operated Ca(2+) entry with a low amplitude and relatively slow kinetics is a main extracellular Ca(2+) entryway into skeletal muscle. Herein, recent studies on extracellular Ca(2+) entry into skeletal muscle are reviewed along with descriptions of the proteins that are related to extracellular Ca(2+) entry and their influences on skeletal muscle function and disease.